Learning about learning: An exploration into the effects of self- and peer-assessment on metacognition in the Mathematics classroom. - Goemans, N (2019)
This action research project sought to explore the effects of formative self- and peer-assessment on the metacognition of a class of fifteen Grade 8 students over a period of fourteen weeks. Weekly problem-solving tasks were assessed quantitively and qualitatively by students and their peers, which prompted peer feedback and discourse, as well as self-reflection. An analysis of assessment scores, in conjunction with data obtained from interviews, questionnaires and group discussions, suggests that consistent, guided peer- and self-assessment promotes the development of metacognitive knowledge and skills in students.